Deificational Hermeneutics as Theological Interpretation: A Theological Exegesis on 2 Peter 1:1–11 - Jacob Chengwei Feng (Religions)
This paper explores the parallel emergence of two theological movements that share ecumenical insights: Theological Interpretation of Scripture (TIS) and deification. It identifies their intrinsic connections to creeds and draws upon their recent scholarly convergence. By highlighting the absence of a robust deificational hermeneutics within the realm of theological interpretation, this paper aims to address that gap by advocating for a deificational hermeneutics that serves the interests of theological interpretation. This argument is founded on three vital theological insights: (1) similar to creeds, the theology of deification is essential to Christian theology with significant ecumenical value, (2) the imago Dei acts as a unifying framework, and (3) readerly formation is central to theological interpretation. Furthermore, through exegetical analysis of 2 Peter 1:1–11, this essay reveals aspects that would remain obscured without the “prism” of deification.